Strategi Kontraktor G7 di Malaysia dalam Menembusi Pasaran Antarabangsa - Jamaludin, Fuoad Haqiemi Bulqiah; Yahya, Mohd Yamani (Research in Management of Technology and Business, 2022)
The construction industry is one of the catalyst sectors that contribute to the development of a country. Success after success has been created by companies and construction firms in Malaysia not only in the local market but also internationally. However, based on international project construction statistics released by the Malaysian Construction Industry Development Board (CIDB) shows a decline in the number of companies and firms offering construction services abroad over the past decade. Therefore, this study was carried out to identify the causes of failure of G7 contractors and the strategies used by G7 contractors in penetrating the international market. The scope of this study is focused on G7 grade contractors. The research instrument used is a structured interview and the data is analyzed using the descriptive analysis method. The research findings that have been found show some of the causes of contractor failure in the international market. Among the causes that have been identified from this study are generating constraints and high financing costs, the rise and fall of the national currency exchange rate, less productivity from construction workers, less involvement from suppliers and local construction experts, different construction laws. Also listed in the reasons for the failure of G7 contractors in penetrating the international market is the burdensome tax system and the existence of fierce international competition from construction experts who have begun to participate. While the results of the study for the strategy carried out by G7 contractors in penetrating the international market have several effective steps. Therefore, this study is important to help G7 contractors in identifying failures in the international market and also identifying effective strategies in penetrating the international market.